Local reinforcing of footing supported in the destroyed rock massif - Sakhno, I; Isayenkov, O; Rodzin, S (National Mining University, 2017)
Purpose. Justification of feasibility of non-explosive destruction of hard rock during in-seam workings based on the obtained dependences related to changes of physical and mechanical properties of non-explosive destructive mixtures (NDM) in the process of hydration in borehole charges causing crack growth in the near-hole area. Methods. Mine in-situ observations at gauge stations were used to determine dynamics of footing bulging. Photofixation method allowed to record discrete state of rocks in the footing during the repair works. The optimal layout for reinforcing the footing was developed in laboratory conditions on structural models by the analysis of longitudinal and transverse system deformations, and by studying the volume of rocks squeezed into the cavity simulating the working. Findings. It has been experimentally proved that the footing rocks have a block discrete structure at a distance of at least half the width of inelastic deformations zone. The empirical dependences are obtained, describing footing bulging and horizontal compaction of rocks under the influence of loading, as a result of the disturbance of the rocks equilibrium state by mining operations for consolidated and non-consolidated rocks. Originality. Formation of a consolidated zone in the form of a straight prism with the vertex of its base triangle facing footing allows to reduce compaction of rocks under the mine by 20%, the footing bulging by 41.8%, and to decrease the volumes of rocks deformed in the working cavity by 41.5%. Practical implications. The obtained results, with accuracy sufficient for practical application, can be used to develop new ways of ensuring stability of footing in cases when rocks have a high degree of destruction. The proposed scheme of local reinforcing, provided its parameters are theoretically justified, can be realized in mine workings with bulging to more than 500 mm. This will help slow the rate of footing deformations and improve the state of workings in difficult mining and geological conditions.

Мета. Обґрунтування доцільності локального зміцнення порід підошви виробок, що підтримуються в зоні розрушених порід, виходячи із залежностей зміни горизонтального ущільнення порід підошви та їх підняття в порожнину виробок для різних схем локального зміцнення. Методика. Шахтними натурними спостереженнями на замірних станціях встановлено динаміку здимання підошви. Методом фотофіксації зафіксовано дискретний стан порід в підошві виробки під час ремонтних робіт. В лабораторних умовах на структурних моделях в результаті аналізу повздовжніх і поперечних деформацій системи та об’ємів порід, що були видавлені в порожнину, що імітує виробку, встановлено найкращу схему зміцнення порід підошви за наведених умов. Результати. Експериментально доведено, що породи підошви виробки на відстані не менше половини ширини зони непружних деформацій мають блочно-дискретну будову. Отримано емпіричні залежності підняття підошви й горизонтального ущільнення порід під впливом навантаження в результаті порушення рівноважного стану порід гірськими роботами для укріплених і неукріплених порід. Наукова новизна. Формування в підошві виробки, що підтримується у зруйнованому масиві, укріпленої зони в формі прямої призми з вершиною трикутника її основи, зверненою до підошви виробки, дозволяє на 20% знизити ущільнення порід під виробкою, знизити підняття порід підошви на 41.8%, скоротити об’єми порід, що деформуються в порожнину виробки, на 41.5%. Практична значимість. Отримані результати, з достатньою для практичного застосування точністю, можуть використовуватися для розробки нових способів забезпечення стійкості підошви виробок у випадках, коли породи мають великий ступінь руйнування. Запропонована схема локального зміцнення, за умови теоретичного обґрунтування її параметрів, може бути реалізована в гірничих виробках з підняттям підошви вище 500 мм. Це сприяє уповільненню швидкостей деформацій підошви і покращенню стану виробок в складних гірничо-геологічних умовах.

Цель. Обоснование целесообразности локального укрепления пород почвы выработок, поддерживаемых в зоне разрушенных пород, исходя из зависимостей изменения горизонтального уплотнения пород почвы и их поднятия в полость выработок для различных схем локального укрепления. Методика. Шахтными натурными наблюдениями на замерных станциях установлена динамика пучения почвы. Методом фотофиксации отмечено дискретное состояние пород в почве выработки во время ремонтных работ. В лабораторных условиях на структурных моделях в результате анализа продольных и поперечных деформаций системы и объемов пород, которые были выдавлены в полость, имитирующую выработку, установлено лучшую схему укрепления пород почвы при описанных условиях. Результаты. Экспериментально доказано, что породы почвы выработки на расстоянии не менее половины ширины зоны неупругих деформаций имеют блочно-дискретную структуру. Получены эмпирические зависимости поднятия подошвы и горизонтального уплотнения пород под воздействием нагрузки в результате нарушения равновесного состояния пород горными работами для укрепленных и неукрепленных пород. Научная новизна. Формирование в почве выработки, поддерживаемой в разрушенном массиве, укрепленной зоны в форме прямой призмы с вершиной треугольника ее основания, обращенной к подошве выработки, позволяет на 20% снизить уплотнение пород под выработкой, уменьшить пучение пород почвы на 41.8%, сократить объемы, деформируемых в полость выработки пород, на 41.5%. Практическая значимость. Полученные результаты, с достаточной для практического применения точностью, могут использоваться для разработки новых способов обеспечения устойчивости почвы выработок в случаях, когда породы имеют большую степень разрушения. Предложенная схема локального укрепления, при условии теоретического обоснования ее параметров, может быть реализована в горных выработках с пучением более 500 мм. Это будет способствовать замедлению скоростей деформаций почвы и улучшению состояния выработок в сложных горно-геологических условиях.
Keywords: rocks; destruction; pressure; stress; bulging